Training Basic Microsoft Office Dalam Mengelola Administrasi Pada Yayasan Kopia Raya Insani - Faizah, Siti; Pudjiarti, Eni; Sofica, Verra; Rudianto, Biktra (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2022)
In the current era, the use of computer applications almost all office work requires it. The development of technology, especially computer applications at this time is very helpful in processing administrative data, so that the data obtained can be arranged neatly and easily understood. One of them is administrative data processing at the Kopia Raya Insani Foundation which requires applications that support so that the data displayed can be understood because at this time some of the administrative data displayed is still fairly manual, the use of Microsoft Office applications in Foundation data processing is still not optimally used due to several reasons. Foundation administrators still do not understand the use of the application used. Microsoft office itself is a software application that is used to process, store, and combine data in the form of documents. The data that can be processed are digital data in the form of letters, pictures and numbers. This software has a special role in the office sector. Matters related to office data will be processed and stored briefly and in detail in Microsoft Office. The method used in providing education regarding the basic use of Microsoft Office is carried out by holding workshops on community service activities so that participants consisting of foundation administrators who will process the foundation's administrative data will be more familiar with the use of Microsoft Office applications to help process administrative data to make it more neat and tidy. easy to understand.